Role of Rab GTPase proteins in cell wall deposition and potential use of rabA mutants in bioenergy crops - Lunn, Daniel (2013)
It has long been known that fossil fuels are a finite source of energy. With this in mind research has turned to the development of renewable energy sources. One solution is the conversion of biomass to useable energy sources. These resources are located in the cell walls of currently available agronomic crops in the form of complex biopolymers, lignocelluloses, which are highly recalcitrant. In the following thesis I explore the novel mechanism of Impacting cell wall composition using mutants involved in trafficking to the cell wall. The following work shows that Rab GTPasemutants impact on cell wall deposition, with specific sub-clades impacting particular cell wall polymers. I then go on to show these mutants have significant effect on recalcitrance and thus increase saccharification of the biomass, without impacting on agronomic properties. Finally I go on to show the same impact on cell wall composition in a presumed orthogolous Rab in tomato. These findings all have significant Implications in the fields of Intracellular trafficking, cell wall biology and bioenergy.